ROCK1 in AgRP neurons regulates energy expenditure and locomotor activity in male mice - Huang, Hu (2013)
Normal leptin signaling is essential for the maintenance of body weight homeostasis. Proopiomelanocortin- and agouti-related peptide (AgRP)-producing neurons play critical roles in regulating energy metabolism. Our recent work demonstrates that deletion of Rho-kinase 1 (ROCK1) in the AgRP neurons of mice increased body weight and adiposity. Here, we report that selective loss of ROCK1 in AgRP neurons caused a significant decrease in energy expenditure and locomotor activity of mice. These effects were independent of any change in food intake. Furthermore, AgRP neuron-specific ROCK1-deficient mice displayed central leptin resistance, as evidenced by impaired Signal Transducer and Activator of Transcription 3 activation in response to leptin administration. Leptin's ability to hyperpolarize and decrease firing rate of AgRP neurons was also abolished in the absence of ROCK1. Moreover, diet-induced and genetic forms of obesity resulted in reduced ROCK1 activity in murine arcuate nucleus. Of note, high-fat diet also impaired leptin-stimulated ROCK1 activity in arcuate nucleus, suggesting that a defect in hypothalamic ROCK1 activity may contribute to the pathogenesis of central leptin resistance in obesity. Together, these data demonstrate that ROCK1 activation in hypothalamic AgRP neurons is required for the homeostatic regulation of energy expenditure and adiposity. These results further support previous work identifying ROCK1 as a key regulator of energy balance and suggest that targeting ROCK1 in the hypothalamus may lead to development of antiobesity therapeutics.